Coupling soil/atmosphere interactions and geochemical processes: A multiphase and multicomponent reactive transport approach. (November 2022) - Ahmadi, Navid; Muniruzzaman, Muhammad; Sprocati, Riccardo; Heck, Katharina; Mosthaf, Klaus; Rolle, Massimo
Highlights: Multiphase flow and multicomponent reactive transport in coupled compartments. Impact of atmospheric forcing on gas component transport and geochemical reactions. COMSOL-PhreeqcRM coupling to simulate porous medium/free-flow systems. Key features of the coupled model illustrated with benchmark and application examples. Abstract: The exchange of gas components across the subsurface/atmosphere interface influences multiphase flow and reactive transport in the subsurface and is crucial for many biogeochemical processes, for the emission of greenhouse gases, and for the fate of volatile contaminants. In this study, we present a modeling approach to simulate non-isothermal multiphase flow and multicomponent reactive transport in coupled subsurface/atmosphere compartments. The model is based on a coupled porous medium/free flow domain in which the Navier-Stokes equation is used to describe single-phase (gaseous) flow in the free-flow subdomain and Darcy's law is applied for two-phase flow in the porous medium subdomain (i.e., two-domain approach). The implementation is performed by coupling COMSOL Multiphysics and PhreeqcRM, which enables the investigation of the interplay between multi-physical processes (i.e., flow, mass and heat transport) in the coupled compartments and geochemical reactions in the porous medium. We first present a set of benchmark examples in which key features of the proposed model are tested against other numerical simulators and an analytical solution. Successively, we take advantage of the unique capabilities of the proposed approach to explore conservative and reactive transport of gas components in a coupled porous medium/free flow domain. The results show that the exchange processes between the compartments control the location of reactive zones and the extent of geochemical reactions (i.e., mineral dissolution) by changing the spatiotemporal distribution of fluid phases and enhancing the interphase mass transfer of key gas components such as oxygen and carbon dioxide.